Response of Genotypes of Mungbean and Blackgram to Planting Dates and Plant Population Densities - Aphiphon Pookpakdi; Harisadee Pataradilok (Agriculture and Natural Resources, 1993)
Two sets of plant population vs planting date study were conducted at Kamphaeng Saen Campus of Kasetsart University, Nakorn Pathom province in Thailand, using two genotypes each of mungbean, Chainat 60 and U-thong 1; and black-gram, U-thong 2 and DM 24 in a split plot experiment with three replications. Main plots composed of three series of planting seasons, dry 1989, wet 1989 and dry 1990 while sub plots composed of three plant populations, viz 200,00 ; 400,000 and 800,000 plants per hectare and two genotypes per species arranged in factorial combination within the main plot. It was found that, The yield of blackgram could be further increased when plant population increased from 200,000 to 800,000 plant, ha-1 . In mungbean cv. Chainat 60, yield increases was also found when plant population increased, however, for U-thong 1, the increase in yield as the result of increasing plant population was not obvious.